2018
DOI: 10.1186/s12889-017-5016-y
|View full text |Cite
|
Sign up to set email alerts
|

Brucellosis remains a neglected disease in the developing world: a call for interdisciplinary action

Abstract: BackgroundBrucellosis is an endemic zoonotic disease in most of the developing world that causes devastating losses to the livestock industry and small-scale livestock holders. Infected animals exhibit clinical signs that are of economic significance to stakeholders and include reduced fertility, abortion, poor weight gain, lost draught power, and a substantial decline in milk production. In humans, brucellosis typically manifests as a variety of non-specific clinical signs. Chronicity and recurring febrile co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
314
1
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 364 publications
(327 citation statements)
references
References 44 publications
3
314
1
9
Order By: Relevance
“…Whereas, Sintayehu et al (2015) reported that goats were about four times more likely to be infected than sheep. Franc et al (2018) reported an average prevalence ranging from 0% to 88.8% in sheep and goats in Africa and Asia. Seropositivity values of 6.0% and 7.5% for sheep herds in Duhok and Sumel were higher than the values reported as 0.7% by Reviriego et al (2000) in Spain, 0.9% by Mokhtar et al (2007) in eastern Sudan, 0.8% by Sintayehu et al (2015) in Ethiopia, and 0.9% by Lakew et al (2019) in Ehiopian-Somali pastoral communities.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, Sintayehu et al (2015) reported that goats were about four times more likely to be infected than sheep. Franc et al (2018) reported an average prevalence ranging from 0% to 88.8% in sheep and goats in Africa and Asia. Seropositivity values of 6.0% and 7.5% for sheep herds in Duhok and Sumel were higher than the values reported as 0.7% by Reviriego et al (2000) in Spain, 0.9% by Mokhtar et al (2007) in eastern Sudan, 0.8% by Sintayehu et al (2015) in Ethiopia, and 0.9% by Lakew et al (2019) in Ehiopian-Somali pastoral communities.…”
Section: Discussionmentioning
confidence: 99%
“…and is transmitted to humans through direct contact with infected animals or by consumption of infected, unpasteurized animal‐derived products. The disease is essentially endemic in marginalized populations in low‐income countries, reason why the World Health Organization has recently classified it as a neglected zoonotic disease .…”
Section: Introductionmentioning
confidence: 99%
“…Brucellosis is one of the most common zoonotic infections that negatively affects livestock productivity and leads to lifelong disability [1]. More than half a million new cases of human brucellosis are recorded worldwide every year, although this figure is considered to be largely underreported.…”
Section: Introductionmentioning
confidence: 99%